La retraduction shakespearienne : espace d’accomplissement ou captation contemporaine ? - Julie Vatain-Corfdir (Sillages Critiques)
Shakespeare’s plays no longer get translated into French – they get retranslated (and frequently so). The goal is not to introduce the text for the first time, but to explore it further, perhaps allowing for a closer connection with today’s audiences. This essay looks into the dynamics which underpin retranslation processes, whether they be literary or political, aimed at the dramatic efficiency of the text or supportive of a director’s specific intentions. The essay examines the relationship of translation to time, in order to outline and characterize 21st-century practice. Antoine Berman’s “retranslation hypothesis,” which offers retranslation as a space for gradual accomplishment, is thus confronted with examples of textual choices in several productions of Julius Caesar and Macbeth, in order to interrogate the aesthetics of a truly “contemporary” approach to retranslating Shakespeare.